A New Routing Protocol for Heterogeneous Mobile Ad Hoc Networks - Bahareh Shafaie; Marjan Kuchaki Rafsanjani (Journal of New Results in Science)
– Each Mobile Ad hoc Network (MANET) consists of some independent system contacting with each other wirelessly. Most of routing protocols work well with this hypothesis, that the network is homogeneous and they are not appropriate for Heterogeneous Mobile Ad hoc Networks (HMANET) and they also lose their efficiency in such networks. Homogeneous Mobile Ad hoc Networks are networks in which all nodes have the same sources and capabilities, and this is in contrast with nature of MANETs because nodes are independent and have different sources, capabilities (such as battery lifetime, bandwidth, transmission range,...) and mobility. In this paper, we improve one of proactive routing protocols named OLSR (Optimized Link State Routing Protocol) so that this protocol becomes appropriate for HMANET and do not lose its capability and scalability. In our method, we suggest an algorithm which uses all existing links (unidirectional, bidirectional ) in a network that works within OLSR routing protocol and this causes better use of sources and minimizes MPR (Multipoint Relays) set